The Legal Regulation of the Fictitious Crime in the Omani Legislation Analytical Descriptive Study - Hosnia, Ahmed O.K; Qeshta, Nizar Hamdi; Osman, Shihab Sulaiman Abdalla; Elbashir, Hanan Abd Elmoniem Gubara (Journal of Ecohumanism, 2024)
The fictitious crime is one of the crimes around which there are still many questions, as it represents criminal behaviour with the perpetrator's imagination only. For instance, for someone who wants to seize money, it turns out that the money belongs to him, which requires more detail and knowledge of the way the Omani legislator organizes this crime. Accordingly, the article will attempt to answer the research problem represented in knowing the legal implications of the fictitious crime in the Omani legislation. To achieve the objectives of the article, doctrinal legal research methodology using a qualitative approach was adopted. The article came to the conclusion that the fictitious crime is due to illusions based on the naivety and ignorance of the perpetrator and without involving the truth. So that the perpetrator believes that he/she is committing a criminal act, but the law does not punish him. The article also recommended that the Omani legislator stipulates explicitly that the fictitious crime should not be punished by an independent and clear text so that it leads to non-punishment for the act that a person commits with the intent of committing a specific crime, then it becomes clear that this person’s belief to achieve the result is based on his delusion.